2016
DOI: 10.18632/oncotarget.13588
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of angiogenesis inhibitors in small-cell lung cancer

Abstract: ObjectiveThe purpose of this study was to investigate the efficacy and safety of angiogenesis inhibitors for small-cell lung cancer (SCLC).MethodsTotally, 16 controlled trials (1898 cases) involving angiogenesis inhibitors plus chemotherapy (ACT group) versus chemotherapy alone group (CT group) were identified from PubMed, EMBASE, Cochrane Library and Wanfang Data before March 2016.ResultsCompared with CT group, ACT group obtained a significant benefit on objective response rate (ORR) (RR = 1.34; 95% CI = 1.19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 37 publications
(59 reference statements)
1
5
0
Order By: Relevance
“…Previously, a meta-analysis has shown that the addition of anti-angiogenic drugs would increase the risks of common AEs, such as pain, hypertension, gastrointestinal symptom, metabolic disorders, and neurology. 15 Notably, the safety profile in this study was similar to that of Rh-endostatin or irinotecan/cisplatin monotherapies. These reported AEs were known and also resulted from the nedaplatin/paclitaxel regimen alone, 11 suggesting that the Rh-endostatin may not increase the risks of toxicity in this population.…”
Section: Assessment Analysis and Discussionsupporting
confidence: 53%
“…Previously, a meta-analysis has shown that the addition of anti-angiogenic drugs would increase the risks of common AEs, such as pain, hypertension, gastrointestinal symptom, metabolic disorders, and neurology. 15 Notably, the safety profile in this study was similar to that of Rh-endostatin or irinotecan/cisplatin monotherapies. These reported AEs were known and also resulted from the nedaplatin/paclitaxel regimen alone, 11 suggesting that the Rh-endostatin may not increase the risks of toxicity in this population.…”
Section: Assessment Analysis and Discussionsupporting
confidence: 53%
“…[40] In this study, the pooled results revealed that angiogenesis inhibitors did not improve OS [HR = 0.99 (95% CI 0.88–1.12), P  = 0.91], PFS [HR = 0.87 (95% CI 0.74–1.02), P  = 0.09] or ORR [HR = 0.94 (95% CI 0.74–1.19), P  = 0.89].…”
Section: Discussionmentioning
confidence: 78%
“…In particular, VEGF-A levels have been demonstrated to directly correlate with the microvessel density. Consistently, the combination of angiogenesis inhibitors, like bevacizumab or ziv-aflibercept, with traditional chemotherapy, significantly improved the overall response rate (ORR) and progression-free survival (PFS) of patients with SCLC [98].…”
Section: Lung Cancermentioning
confidence: 89%